COMPARISON OF THE RESULTS OF RESEARCH OF MILK COWS WITH MASTIDINOVOJ PROBE AND METHOD OF CULTURAL THE SELECTION OF STAPHYLOCOCCUS AUREUS - Бердник, В. П.; Тімченко, О. В. (Scientific Progress & Innovations, 2013)
In comparative terms the results of researches 85 samples of milk cows using mastydynovoyi samples and cultural method for the selection Staphylococcus aureus. With mastydynovoyi samples obtained positive results in 20 (23.5 %) cases, and cultural methods - 34 (40.0 %). Of the 41 samples of milk volume of 10.0 ml of culture isolated St. aureus in 34 (82.9 %) cases, 1.0 ml – 25 (61.0 %) and 0.1 ml – 22 (53.6 %) cases. In 13 (65.0 %) of 20 samples of milk, which reacted with mastydynom, the results of both tests coincided, in 7 (35.0 %) – no.